Growth, structure and friction behavior of the nanocomposite hard coatings WS2-Ti (2010)
Thin films of tungsten bisulfide (WS2) and tungsten bisulfide nanocomposites doped with Titanium (WS2-Ti) were deposited on silicon substrates, varying the substrate temperature and the potency of the targets by means of co-sputtering magnetron, with in order to obtain different concentrations of Ti in the nanocomposite. The coatings were analyzed by means of X-ray diffraction (XRD), high resolution scanning electron microscopy (HRSEM / EDS) and high resolution transmission electron microscopy (HRTEM), to observe the change in crystallinity and morphology of the coatings, with respect to the percentage of Ti induced and the change in the substrate temperature. In the co-sputtering process, the inclusion of Ti prevents crystallization of the WS2 by forming dispersed amorphous nanocrystals (1–3 nm). The friction tests carried out by means of a disk pin (POD), at low temperatures, show that the coatings deposited at room temperature and low concentrations of Ti (between 5 and 14% at) have better shelf life than the coatings of WS2 pure, but no significant changes in the coefficient of friction (COF) were observed. The same effect is observed in high temperature friction tests (500 ° C) with major changes in COF. To study the mechanisms of solid lubrication, the samples were prepared by means of focused ion beam (FIB) and analyzed by means of Raman spectroscopy determining the behavior of the deformation on the surface and the formation of tribochemical products in the wear traces . Observing the formation of WO3 on the surface during wear (tribo-oxidation) and its transfer to the counter face of the pair (generation of a third body). Doping the material with Ti, producing a nanocomposite, is a procedure that improves the tribological properties of the material in humid environments and high temperatures, reducing oxidation and improving the life of the pieces. This way of obtaining better working conditions has been poorly studied in detail and a reaction mechanism is presented that allows explaining this phenomenon using innovative analysis techniques such as FIB.